PENERAPAN METODE PERMAINAN DALAM MENINGKATKAN TEKNIK PASSING BAWAH BOLA VOLI SISWA SEKOLAH DASAR: APPLICATION OF GAME METHODS IN IMPROVING DOWN PASSING TECHNIQUES OF VOLLEYBALL BASIC SCHOOL STUDENTS - Marzuki, Gilang Achmad; Setyawan, Agung (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
The purpose of this study is to help fifth grade students of SDN Pradah Kali Kendal 1 Surabaya develop their Volleyball under-passing skills using play-based techniques.  This study uses descriptive methods and adheres to the methodology of Classroom Action Research (CAR).  Thirty-one fifth graders of SDN Pradah Kali Kendal 1 Surabaya became the subject of research.  Observation sheets and process tools are used for direct observation to collect data. With an average score of 63.06 and a mastery rate of 38.71% (12 students) in the pre-cycle stage, the results showed an improvement in learning outcomes.  The mastery level rose to 58.06% (18 students) with an average score of 70.70 in the first cycle and 93.55% (29 students) with an average score of 78.54 in the second cycle.  The game-based approach successfully improved children's volleyball skills, according to data analysis